Measuring anti-convulsant levels in the accident and emergency department. Issue 2 (June 1986) - McGlone, R; Pritty, P
Abstract : A prospective study involving 57 epileptic adults who presented to the Derbyshire Royal Infirmary Accident and Emergency Department with fits has shown that 57% were in the sub therapeutic ranges.